President Foote (1930)
1 photograph : sepia toned 13.5 x 8 cm John Cormier presenting Samuel J. Foote's salmon. They are standing in front of the Fomowa Clubhouse. Title from album caption. Samuel J. Foote (1873-1936) was born in Grand Bank in 1873. Foote was called to the Newfoundland Bar in 1899 and went to practice with Sir James Winter. Foote entered into politics in 1904. Foote died on December 8, 1936.John Cormier sold the house and land at Forks Pool on the Grand River, Codroy, July 11, 1914 to the FOMOWA Fishing Club. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.